2020
DOI: 10.3390/vaccines8030528
|View full text |Cite
|
Sign up to set email alerts
|

Near-Infrared Photoimmunotherapy Combined with CTLA4 Checkpoint Blockade in Syngeneic Mouse Cancer Models

Abstract: Near infrared photoimmunotherapy (NIR-PIT) is a newly developed and highly selective cancer treatment that induces necrotic/immunogenic cell death. It employs a monoclonal antibody (mAb) conjugated to a photo-absorber dye, IRDye700DX, which is activated by NIR light. Tumor-targeting NIR-PIT is also at least partly mediated by a profound immune response against the tumor. Cytotoxic T-lymphocyte antigen-4 (CTLA4) is widely recognized as a major immune checkpoint protein, which inhibits the immune response agains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 31 publications
0
22
0
Order By: Relevance
“…CD44 is overexpressed in various cancers; however, it is also expressed on non-cancer cells in the TME, including some populations of activated lymphocytes [ 20 , 21 ]. Our previous study showed that CD44-targeted NIR-PIT indeed killed CD44-expressing CD8+ T cells, sparing CD44-negative CD8+ T cells which can be activated later on [ 22 ]. We actually observed additional multiclonal T cell expansion and infiltration after CD44-targeted NIR-PIT [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…CD44 is overexpressed in various cancers; however, it is also expressed on non-cancer cells in the TME, including some populations of activated lymphocytes [ 20 , 21 ]. Our previous study showed that CD44-targeted NIR-PIT indeed killed CD44-expressing CD8+ T cells, sparing CD44-negative CD8+ T cells which can be activated later on [ 22 ]. We actually observed additional multiclonal T cell expansion and infiltration after CD44-targeted NIR-PIT [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…CD44-targeted NIR-PIT significantly suppressed tumor progression and prolonged survival in CD44-expressing syngeneic mouse models of oral squamous cell carcinoma [ 72 ]. Moreover, combined CD44-targeted NIR-PIT with programmed cell death protein 1 (PD-1) or CTLA4 checkpoint blockade was more effective in combination than as single therapies in syngeneic mouse models, including a minimally immunogenic tumor [ 21 , 73 , 74 ]. Combined CD44-targeted NIR-PIT with PD-1 blockade eradiated more than 70% of established tumors [ 21 ].…”
Section: Nir-pit Targeting Cancer Cellsmentioning
confidence: 99%
“…NIR-PIT has been successfully applied for EGFR expressing tumors (e.g., skin cancer [10] , lung cancer [17] , and breast cancer [8] ), human epidermal growth factor receptor 2 (HER2) (e.g., gastric cancer [18] and breast cancer [19] ), prostate-specific membrane antigen (PSMA) (e.g., prostate cancer) [20] , carcinoembryonic antigen (CEA) (e.g., colon cancer) [21] , [22] , [23] , mesothelin (MSLN) (e.g., mesothelioma, pancreatic, and ovarian cancers) [6] , Glypican 3 (GPC3) (e.g., hepatocellular carcinoma) [24] , CD20 (e.g., malignant lymphoma) [5] , tumour‐associated calcium signal transducer 2 (TROP2) (e.g., cholangiocarcinoma) [25] , delta-like protein 3 (DLL3) (e.g., small cell lung cancer) [22] , podoplanin (PDPN) (e.g., mesothelioma) [23] and G-protein coupled receptor 87 (GPR87) (e.g., lung cancer and mesothelioma) [24] , as shown in the Table 1 . NIR-PIT can also be used for programmed death-ligand 1 (PD-L1) expressing cancer cells [26] , for CD25 for regulatory T cells (Tregs) [ 7 , 27 , 28 ], and CD44 [ 4 , 12 , 16 , 29 , 30 ] and CD133 for cancer stem cells [31] .…”
Section: Successful Preclinical Applications Of Nir-pitmentioning
confidence: 99%